2018
DOI: 10.1016/j.immuni.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor IRF8 Orchestrates the Adaptive Natural Killer Cell Response

Abstract: Natural killer (NK) cells are innate lymphocytes that display features of adaptive immunity during viral infection. Biallelic mutations in IRF8 have been reported to cause familial NK cell deficiency and susceptibility to severe viral infection in humans; however, the precise role of this transcription factor in regulating NK cell function remains unknown. Here, we show that cell-intrinsic IRF8 was required for NK-cell-mediated protection against mouse cytomegalovirus infection. During viral exposure, NK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 74 publications
9
94
0
Order By: Relevance
“…This hypothesis was strengthened by the study of Irf8 −/− mice, who were found to have decreased frequency of terminally mature NK cells in peripheral blood and spleen . Further study of these mice showed that they are particularly susceptible to LCMV infection and malignancy and that generation of adaptive NK cells in these mice following infection is impaired . In both murine and human NK cells, IRF8 is up‐regulated in response to cytokine signaling, and in mice, this leads to Stat4‐mediated binding of Irf8 to the cell cycle regulator Zbtb32.…”
Section: Classical Nkd (Cnkd)mentioning
confidence: 99%
See 3 more Smart Citations
“…This hypothesis was strengthened by the study of Irf8 −/− mice, who were found to have decreased frequency of terminally mature NK cells in peripheral blood and spleen . Further study of these mice showed that they are particularly susceptible to LCMV infection and malignancy and that generation of adaptive NK cells in these mice following infection is impaired . In both murine and human NK cells, IRF8 is up‐regulated in response to cytokine signaling, and in mice, this leads to Stat4‐mediated binding of Irf8 to the cell cycle regulator Zbtb32.…”
Section: Classical Nkd (Cnkd)mentioning
confidence: 99%
“…Further study of these mice showed that they are particularly susceptible to LCMV infection and malignancy and that generation of adaptive NK cells in these mice following infection is impaired . In both murine and human NK cells, IRF8 is up‐regulated in response to cytokine signaling, and in mice, this leads to Stat4‐mediated binding of Irf8 to the cell cycle regulator Zbtb32. In this way, viral infection or expansion in response to tumor challenge leads to Irf8‐mediated NK cell expansion and generation of the NK cell memory pool …”
Section: Classical Nkd (Cnkd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Functionally, STAT4 acts in part by directing a ‘permissive’ chromatin state, likely through the recruitment of histone remodeling enzymes, around target gene loci. Indeed, H3K4 trimethylation at the Runx , Cbfb , and Irf8 promoters was recently shown to occur in a STAT4‐dependent manner during NK cell activation in vitro . The related TF, STAT1 also contributes to the expansion of MCMV‐specific Ly49H + NK cells, acting downstream of type 1 interferon (IFN‐I) signals that serve to protect NK cells from NKG2D‐dependent fratricide .…”
Section: Transcription Factors That Regulate Effector and Memory Nk Cmentioning
confidence: 99%